Internalisasi Nilai Pendidikan Agama Islam melalui Pendidikan Karakter - Alivia Fatikatuz Zahroh; Muhamad Sidiq Asyhari (Journal on Education, 2024)
This research aims to explore the process and impact of implementing the internalization of Islamic Religious Education values through character education at SDN I Sukoharjo, Bandung Sub-District, Tulungagung District. The character education program at the school is conducted through religious habituation practices such as performing the Duha prayer, memorizing short verses of the Quran and reciting tahlil, commemorating Islamic holidays, Friday charity contributions, and others. It is emphasized that achieving the goals of internalizing Islamic Religious Education values greatly depends on simultaneously conducting religious activities. The research method employed is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research informants consist of the school principal, Islamic Religious Education teachers, homeroom teachers, and students of SDN I Sukoharjo. The research findings indicate that the process of internalizing these values progresses well through three stages: transformation of values, transaction of values, and internalization of values. The impact of this internalization is reflected in increased worship awareness, changes in attitudes and behaviors, as well as improved understanding and knowledge of religion among students.